Chiral pyridine-N-heterocyclic carbene based palladacycle for homogeneous catalysis : synthesis, characterization and application. - Ng, Kim Hong. (2010)
Optical resolution (using enantiopure amino acids) was used as a mean to resolve a racemic six-membered bidentate pyridine-N-heterocyclic based palladacycle. Two different solvent systems were found to be able to crystallize out one of the diastereomer, (SC,SC)-5 successfully, leaving the mother liquor to be enriched with the other diastereomer, (RC,SC)-5. After which, the optically pure (R)-4 and (S)-4 were achieved via the removal of the chiral auxillary by stirring in aqueous 1M hydrochloric acid. Crystallizations of the (R)-4 and (S)-4 dichloropalladacylce were ineffective due to the insufficient solubility of the palladacycles. Instead, crystallization of (R)-6 and (S)-6 were performed. The absolute configurations of all the crystals were determined by X-ray diffraction studies. The catalytic activity of (S)-6 was tested in asymmetric allylic alkylation and was compared with four other palladacycles (R)-9, (S)-9, (R)-10 and (S)-10 to study the electronic and solvent effect.